An Essay on Islam and Human Rights: With Special Reference to Qur’anic Perspective - Kaur, Paramjit (International Journal of Advanced Research in Peace, Harmony and Education, 2021)
Islam is a universal and inspired religion. Islam is the second most widely practiced religion in the world after Christianity. It is a religion based on the ideology of the Qur’an. It is completely dedicated to the oneness and supremacy of Allah. From the earliest times man has been in search of truth. Muslims are one of those who have accepted the messages of the spiritual prophets in an effort to reach reality. Islam is also called the primary religion. It is a prophetic and Semitic religion. Its arrival is believed to have started with the arrival of Hazrat Adam (PBUH) and Eve. After this many prophets came and the last prophet was Hazrat Muhammad . This study seeks to consider the context of human rights in the light of the Qur’an.In this research article an attempt has been made to study the existence of human and human rights in Islam. Various aspects of human rights have been studied, including the Qur’anic qutoes and the special references to various scholars. The rights under the independent Charter for the basic rights of citizens under the Islamic State have been briefly studied, so that Islamic human rights can be analyzed. How to cite this article:  Kaur P. An Essay on Islam and Human Rights: With Special Reference to Qur’anic Perspective. Int J Adv Res Peace Harm Edu 2021; 6(1): 1-4. DOI: https://doi.org/10.24321/2455.9326.202101